2015
DOI: 10.3390/w7052358
|View full text |Cite
|
Sign up to set email alerts
|

Model Calibration Criteria for Estimating Ecological Flow Characteristics

Abstract: Quantification of streamflow characteristics in ungauged catchments remains a challenge. Hydrological modeling is often used to derive flow time series and to calculate streamflow characteristics for subsequent applications that may differ from those envisioned by the modelers. While the estimation of model parameters for ungauged catchments is a challenging research task in itself, it is important to evaluate whether simulated time series preserve critical aspects of the streamflow hydrograph. To address this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 33 publications
4
58
0
Order By: Relevance
“…Estimated streamflow characteristics are prone to significant errors when calculated from simulated time series (Murphy et al, 2013;Shrestha et al, 2014;Vis et al, 2015). This is due in part to the objective functions used for evaluating the model error such as the commonly used model efficiency (Nash and Sutcliffe, 1970) or volume error, which do not ensure that a model reproduces particular streamflow characteristics.…”
Section: S Pool Et Al: Streamflow Characteristics From Modeled Runomentioning
confidence: 99%
See 2 more Smart Citations
“…Estimated streamflow characteristics are prone to significant errors when calculated from simulated time series (Murphy et al, 2013;Shrestha et al, 2014;Vis et al, 2015). This is due in part to the objective functions used for evaluating the model error such as the commonly used model efficiency (Nash and Sutcliffe, 1970) or volume error, which do not ensure that a model reproduces particular streamflow characteristics.…”
Section: S Pool Et Al: Streamflow Characteristics From Modeled Runomentioning
confidence: 99%
“…These objective functions subsequently guide model parameter calibration, which strongly influences the simulated hydrograph (for an overview, see Pfannerstill et al, 2014) in terms of annual, seasonal, and monthly volumes and magnitudes. For example, Vis et al (2015) compared model simulation from calibrations based on only the model efficiency with calibrations based on the combination of multiple objectives such as model efficiency, model efficiency of log-transformed flow, volume error, and Spearman rank correlation. All these calibration approaches tended to overestimate low flows and underestimate medium and high-flow-related SFCs.…”
Section: S Pool Et Al: Streamflow Characteristics From Modeled Runomentioning
confidence: 99%
See 1 more Smart Citation
“…Shrestha et al [30] suggested that the ability of the models to replicate different components of the hydrograph simultaneously was not clear. Especially quantification of streamflow characteristics using hydrological models in ungauged catchments remains a challenge [31,32]. In spite of its disadvantages, this approach is commonly used to simulate and calculate the relative impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Because the HBV-Light source code was not available, the authors have developed the IHBV model in FORTRAN. Further information on HBV and its applications can be found in related references [41,[49][50][51]. …”
Section: Improved Hbv Model Descriptionmentioning
confidence: 99%